The use of ringing data in the study of climatic influences on common passerines - Jansen, Dorine Yvette Manon (Department of Statistical Sciences, 2016)
To understand the potential impact of forecasted increases in climatic variability we need to determine the impact of climatic stochasticity on demographic rates. This thesis used available long-term ringing data collected by volunteers, augmented by data from research projects, to investigate the influence of climatic variation on survival of 10 common passerines in southern Africa. Through sheer numbers common species are fundamental to ecosystem functioning. Migratory species are subject to climatic stochasticity in breeding and wintering grounds, and during migration. In a population of African Reed Warblers Acrocephalus baeticatus (an azonal wetland specialist) a capture-mark-recapture model correlated higher temperature in the breeding grounds with higher adult survival (1998-2010), but - contrary to expectations - not wetter winters. A spatial analysis using a multi-state model in a Bayesian framework did not link survival in populations across southern Africa to environmental seasonality. However, as hypothesised, migratory populations appeared to survive better than sedentary populations. Increased climatic variation could synchronize survival of species assemblages and colonies in meta-populations. I investigated a 3-species assemblage in climatically stable fynbos (2000-2007) and a 4-species assemblage in more seasonal wetland (1999-2013) with a hierarchical model, run in WinBUGS, with a temporal, synchronous (common) and asynchronous (species-specific) component. Comparison of models with and without climatic covariates quantified the impact of climatic stochasticity as a synchronizing and desynchronizing agent. As expected, the wetland assemblage exhibited more synchronous and asynchronous variation in survival than the fynbos assemblage, but the analysis did not find evidence of climatic forcing. Demographic rates of a population of 25 colonies of a Sociable Weaver Philetairus socius meta-population in savanna near Kimberley did not correlate with climatic indices during 1993-2014. Age-specific survival and fecundity of the largest colony were influenced by climatic variation reinforcing earlier inference that colonies respond differently to environmental stochasticity. The integrated population model using count, ringing, and productivity data enabled the first estimation of annual fecundity, juvenile survival and recruitment. The volunteer data yielded the first estimates of adult survival of two African endemics and estimates of a second population for three other species. A review of volunteer ringing resulted in recommendations to improve its use from a demographic perspective.